Strengthening Msmes of Kedung Aren Banana Chips Through Product or Code to Promote International Marketing - Yunita Making; Siltia Murti; Rasti Kristanti Daramena; Vallentiasafita Tutu Sari; Martinus Budiantara; Kylie The Kai Li; Prashanth Beleya (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
: The empowerment of micro, small, and medium enterprises (MSMEs) plays a crucial role in strengthening local economic resilience, increasing community welfare, and enhancing competitiveness in the digital era. This international community service program focuses on developing the Kedung Aren Banana Chips MSME through the implementation of product-based QR Codes as a digital marketing tool. The program aims to improve digital literacy, strengthen branding, and expand market reach, particularly toward potential international consumers. The activities conducted include training on QR Code creation, guidance on integrating digital information into product packaging, monitoring marketing practices, and evaluating the program’s effectiveness. Feedback from Malaysian partners and participants indicates that optimizing QR Codes with dynamic and informative digital content significantly enhances market accessibility, consumer trust, and promotional effectiveness. The program generates positive economic impacts through increased sales potential, social benefits through improved human resource capabilities, and environmental benefits by reducing the use of printed promotional materials. Overall, the program provides a sustainable foundation for MSME modernization and positions Kedung Aren banana chip products to compete more effectively in both domestic and global markets.